Women’s Perceptions about Glass Ceiling in their Career Development in Local Bureaucracy in Indonesia - Krissetyanti, Eunike Prapti Lestari (UI Scholars Hub, 2018)
Inadequate women representation in upper position Inadequate women representation in upper position in workforce shows the persistence of the glass ceiling phenomenon in women career development. In Indonesia’s bureaucracy, although the number of women civil service in government workforce had increased for recent years, only few numbers of female civil services who have structural positions, especially in upper echelon (high leader position). This problem is more noticeably on the local government bureaucracy. Focus of this study is to identify glass ceiling embodied in the career barriers women civil service in local bureaucracy. This study was conducted using qualitative method. Interviews were conducted against women civil service who held structural position in the provincial government of Special Region of Yogyakarta, and also toward key person related to civil service career development in Local Civil Service Agency of the Province of Special Region of Yogyakarta, and National Civil Service Agency. The study also based on secondary data. Grounded theory approach is used to analyze the data. Finding of this research show using open coding the barriers of women civil service career development can be identified into four categories that is individual, interpersonal, organizational, family, and societal. To find the glass ceiling that faced by women, it is needed to separating artificial barriers (glass ceiling) and natural barriers. Using axial coding, the barriers can be identified into two sub-categories, that is natural barriers and artificial barriers.